The value of neutrophil to lymphocyte ratio and gamma-glutamyl transpeptidase to platelet ratio in patients with hepatocellular carcinoma - Hu, Zuojian (Medicine (Baltimore), 2019)
Our study aimed to evaluate the value of neutrophil to lymphocyte ratio (NLR) and gamma-glutamyl transpeptidase to platelet ratio (GPR) in patients with hepatocellular carcinoma (HCC). A total of 565 patients with pathological diagnosis of HCC were retrospectively analyzed and 414 patients diagnosed with cirrhosis were treated as a control group. All clinical materials were collected from the First Affiliated Hospital of Guangxi Medical University. The preintervention NLR, GPR, and α-fetoprotein (AFP) were significantly higher in HCC patients than in the controls (P(NLR) < .000, P(GPR) < .000, P(AFP) < .000). The NLR and GPR were correlated with the Barcelona clinic liver cancer (BCLC) stages, Child-Pugh grades, and tumor size, but not with Edmondson–Steiner grades. Combined use of NLR or GPR with AFP produced larger area under the curve (AUC) (AUC(NLR+AFP) = 0.916; AUC(NLR+AFP) = 0.953) than NLR (P < .000), GPR (P < .000), or AFP (P < .000) used alone. The preintervention hematologic parameters (NLR and GPR) studied herein were associated with the BCLC stages of HCC. Combined use of NLR or GPR with AFP may improve early detection and diagnosis of HCC.